Tradisi Penetapan 1 Ramadhan dengan Penanggalan Jawa: Kajian Living Hadis atas Komunitas Islam Aboge di Desa Cikakak, Kecamatan Wangon, Kabupaten Banyumas - Nur Laili Nabilah Nazahah Najiyah; Umi Salamah; Khoirun Nisa' (Jurnal Kawakib, 2022)
The Aboge Islamic community has a distinctive feature, namely their calculation system in determining important days by following the teachings of their ancestors. For example, the determination of the 1st of Ramadan. This tradition is very attached to the people of Cikakak Village. In addition, in determining important Islamic days, the Aboge Islamic community only uses the Javanese calendar. The analysis is based on the study of living hadith using a phenomenological approach. There are three important things obtained from this study. First, in determining the 1st of Ramadan, the Aboge Islamic community uses the Javanese calendar with the Aboge calculation system. Second, the Aboge Islamic community is still preserving the traditions of their ancestors, namely establishing the 1st of Ramadan using the Javanese calendar. Third, they believe that what their ancestors commanded is the same as obeying God, as in the hadith.